1998
DOI: 10.3109/03630269809113134
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of β-Thalassemia Major and β-Thalassemia Intermedia in Brazil

Abstract: The development of methodologies to identify the molecular lesions responsible for different types of beta-thalassemia has made it possible to correlate these data with clinical and hematological severity. We examined DNA from 35 patients with beta-thalassemia, residents of the State of São Paulo, Brazil, for some types of genetic modifying factors: beta-thalassemia mutations, the upstream Xmnl GY-globin gene polymorphisms, and alpha-globin gene deletions. Additionally, the beta-like gene cluster haplotypes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
2
5

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 19 publications
1
15
2
5
Order By: Relevance
“…Data obtained in two studies performed in southeast Brazil showed that the most prevalent molecular defect was b 0 -thal owing to the nonsense mutation at codon 39 (C ! T) (8,9). Accordingly, most of the symptomatic patients exhibit a picture of severe transfusion-dependent b-thal major, whereas thalassemia intermedia is very rare (9).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Data obtained in two studies performed in southeast Brazil showed that the most prevalent molecular defect was b 0 -thal owing to the nonsense mutation at codon 39 (C ! T) (8,9). Accordingly, most of the symptomatic patients exhibit a picture of severe transfusion-dependent b-thal major, whereas thalassemia intermedia is very rare (9).…”
Section: Introductionmentioning
confidence: 97%
“…T) (8,9). Accordingly, most of the symptomatic patients exhibit a picture of severe transfusion-dependent b-thal major, whereas thalassemia intermedia is very rare (9). Similarly, Hb S=b-thal double heterozygotes have a severe sickle cell syndrome, quite similar to homozygous sickle cell anemia (8).…”
Section: Introductionmentioning
confidence: 97%
“…The propositus and his mother were found to be heterozygous for a nonsense mutation: the C ® T substitution at the first nucleotide position of the 39 th codon, in exon 2 of the b-globin gene, creates a stop codon resulting in premature termination of the globin chain synthesis. This b-thalassemia mutation is common in the Mediterranean population and is also one of the most frequent b-globin mutations found in Brazil (Fonseca et al, 1998). Another b-globin gene mutation was detected in the propositus and his father: the b104 (G6) arginine residue was replaced by serine [beta 104(G6) Arg ® Ser], resulting in the variant Camperdown Hemoglobin (Hb Camperdown).…”
mentioning
confidence: 99%
“…Although data on the extent of the diversity of hemoglobin disorders in Brazil are incomplete (Old, 2003;Zago and Costa, 1985;Fonseca et al, 1998;Araújo et al, 2003), many b-globin mutant alleles have been detected in patients from different Brazilian regions (Araújo et al, 2003;Fonseca et al, 1998;Grignoli et al, 2000).…”
mentioning
confidence: 99%
See 1 more Smart Citation